A mixed collector system for columbite-tantalite flotation. (15th January 2021) - Cao, Miao; Bu, Hao; Gao, Yude
Highlights: BHA-SIBX mixture was introduced as a mixed collector in columbite–tantalite flotation. BHA-SIBX mixture displayed superior flotation performances than single BHA. BHA-SIBX mixture was a promising collector for fine columbite–tantalite flotation. Abstract: Effective collector is essential in columbite-tantalite flotation from gravity tailings, as well as in the sustainable utilisation of Ta–Nb resources. In this study, benzohydroxamic acid (BHA) and sodium isobutyl xanthate (SIBX) were introduced as a mixed collector system to improve the flotation of columbite–tantalite at reduced cost. An increase in columbite-tantalite recovery was observed in the presence of BHA–SIBX mixtures relative to those with BHA alone. The 3:1 BHA–SIBX mixture exhibited the highest columbite-tantalite recovery. The synergistic enhancement of the flotation performance was attributed to the improved adsorption of the BHA–SIBX mixture on the columbite-tantalite surface compared to that on BHA alone. Batch flotation tests of real ore showed that, compared with BHA (600 g/t), a smaller amount of the BHA–SIBX mixture (400 g/t) was needed to achieve better Ta2 O5 recovery. Additionally, an economic evaluation confirmed the economic efficiency of recovering fine columbite-tantalite from gravity tailings using the mixed BHA–SIBX collector.